Люминесценция активированной вольфрамом керамики MgF2 - Карипбаев Ж. Т.; Мусаханов Д. А.; Тулегенова А. Т.; Мархабаева А. А.; Лисицын В. М. Виктор Михайлович (Оптические технологии, 2017)
Заглавие с титульного экрана